ECOLOGICAL TRIALS OF NEW MAIZE HYBRIDS IN THE CONDITIONS OF VARIOUS MOISTURE SUPPLY - G. Ya. Krivosheev (Зерновое хозяйство России, 2018)
The article presents the results of ecological trials of ten new maize hybrids developed by the ARC “Donskoy” at six points with different moisture supply. According to grain yields there have been identified such valuable for definite conditions hybrids as: ‘Ze 235’ with 5.0 t/ha and ‘Ze 428’ with 6.55 t/ha (ARC “Donskoy”, Zernograd); ‘Ze 182’ with 9.02 t/ha (ARRI of maize, Pyatigorsk); ‘Ze 286’ with 4.92 t/ha (RCG named after P.P. Lukiyanenko, Krasnodar); ‘Ze 428’ with 7.61 t/ha (RPE “Semenovodstvo Kubani”, v. of Ladozhskaya, Krasnodar Area); ‘Ze 331’ with 10.1 t/ha (Agrofirm “Otbor”, v. of Komsomolsky); ‘Ze 428’ with 6.55 t/ha (RusRC “Rossorgo”, Saratov). For the arid conditions there has been recommended the hybrid ‘Ze 428’ with 5.11 t/ha of grain on average at the points with insufficient moisture supply. For the conditions of sufficien moisture supply there has been recommended the hybrid ‘Ze 331’ with 8.06 t/ha at the points with high moisture supply. The new hybrids ‘Ze 182’, ‘Ze 236’, ‘Ze 285’, ‘Ze 286’, ‘Ze 331’, ‘Ze 332’, ‘Ze 333’, ‘Ze 427’, ‘Ze 428’ have been characterized with high responsiveness on the change of growing conditions, regression coefficient (bi) was 1.42–2.02; the hybrid ‘Ze 235’ is found to be an ecologically adaptable genotype (bi = 1). All hybrids belong to ecologically stable genotypes (σd2=0,13–0,74). The hybrids ‘Ze 235’ and ‘Ze 331’ showed the highest index of drought tolerance (72.7 and 67.3% respectively). The early ripening hybrid ‘Ze 182’ (FAO 180), the middle-ripening hybrid ‘Ze 286’ (FAO 250), the middle ripening hybrid ‘Ze 331’ (FAO 300) and the middle-late hybrid ‘Ze 428’ (FAO 400) are the most promising hybrids for practical use according to such their economic-valuable traits as grain productivity, harvesting moisture of grain, resistance to lodging, resistance to smut viruses and ear attachment height.